In vitro Selection of Enteric Microflora for Potential Use as a Competitive Exclusion Culture Against Campylobacter in Poultry - Bhaskaran, H.P.; Donoghue, A.M.; Arsi, K.; Wooming, A.; Reyes-Herrera, I.; Bielke, L.R.; Tellez, G.; Byrd, J.A.; Blore, P.J.; Hargis, B.M.; Donoghue , D.J. (International Journal of Poultry Science, 2011)
The administration of nonpathogenic microflora in neonatal poultry has been employed to reduce or eliminate the colonization of enteric pathogens. This concept, also called Competitive Exclusion (CE), although effective against Salmonella, has not consistently worked against Campylobacter. Most CE cultures are developed by randomly collecting enteric bacteria without any preselection criteria for bacteria. It may be possible to enhance the efficacy of a CE against Campylobacter by preselecting enteric microflora with the ability to inhibit Campylobacter, in vitro. With this goal, an assay was developed to test individual isolates with the ability to reduce or eliminate Campylobacter growth, in vitro. Individual isolates (n = 137) were collected from ceca of both juvenile and adult poultry and tested for efficacy against Campylobacter. Isolates were serially diluted (104 or 105 CFU/well) and added to 96 well polystyrene plates containing 1 x 104 CFU C. jejuni or C. coli/well. Plates were incubated at 42°C in a microaerophilic environment for 24-48 h. Following incubation, a 1 μl loop from each well was streaked onto Campy-Cefex agar plate and incubated at 42°C in a microaerophilic environment for 24-48 h. Twenty-three isolates were identified with the ability to inhibit C. jejuni or C. coli growth in vitro. This research demonstrates that it is possible to pre-screen enteric isolates for Campylobacter inhibition for use as competitive exclusion cultures.